Can Digital Research be an Alternative Method during the COVID-19 Pandemic in Indonesia? - Bahtiar Rifai; Meilinda Sari Yayusman; Vera Bararah Barid (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2021)
Unprecedented COVID-19 global pandemic entails uncertain conditions, which lead people to seek alternative solutions to make activities running accordingly. Limited movements due to travel restriction and health protection confine people’s activities, including the research process. Postponing research activities is arguably not the best solution for scholars, mainly while conducting data collection. In social and humanities research, researchers mostly undertake data collection through field studies and face-to-face communications prior to the pandemic. Social distancing procedures, however, encourage people to avoid close contacts and cancel visit plans. Thus, researchers are necessary to find an alternative method during uncertainty situation. Digital research method (DRM) seems to be a plausible way to keep research ongoing, although the implementation of that method in the developing countries’ research activities, compared to the developed countries, remains lagging behind. This research aims to position DRM amidst the pandemic situation and show possibilities in using this method as an alternative in the developing countries by taking Indonesia as a case study. Results show that to make DRM works in Indonesia, some requirements need to be fulfilled to meet academic standards, and whether relevant or not the research topic applies to be processed utilizing digital method are also essential to be considered.